2020
DOI: 10.1101/2020.07.09.194399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of STING due to COPI-deficiency

Abstract: COPA syndrome is caused by loss-of-function mutations in the COP-α subunit of coatomer protein complex I (COPI), which participates in retrograde vesicular trafficking of proteins from the Golgi to the endoplasmic reticulum (ER). Disease manifests early in life with arthritis, lung pathology, kidney dysfunction and systemic inflammation associated with NF-κB activation and type I interferon (IFNαβ) production. Here, we generated in vitro models for COPA syndrome and interrogated inflammatory signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In our study, we have identified STING as a novel target of Palbociclib. It has been well documented that STING plays a crucial role in promoting anti‐tumor immunity by activating innate immunity, boosting DC maturation (Curran et al , 2016) and activating natural killer cells (Nicolai et al , 2020; preprint: Steiner et al , 2020) as well as CD8 + T cells (Sen et al , 2019). It is, therefore, highly likely that CDKi‐mediated inhibition of STING activation may impair STING‐mediated anti‐tumor immunity, which will bring attention to potential drawbacks in the clinical application of Palbociclib and its structural analogs in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have identified STING as a novel target of Palbociclib. It has been well documented that STING plays a crucial role in promoting anti‐tumor immunity by activating innate immunity, boosting DC maturation (Curran et al , 2016) and activating natural killer cells (Nicolai et al , 2020; preprint: Steiner et al , 2020) as well as CD8 + T cells (Sen et al , 2019). It is, therefore, highly likely that CDKi‐mediated inhibition of STING activation may impair STING‐mediated anti‐tumor immunity, which will bring attention to potential drawbacks in the clinical application of Palbociclib and its structural analogs in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nerveless, cGAS inhibitors still can be a good complement to therapeutic regimens for the treatment of DNA-dependent autoimmune diseases. Besides, it was reported that TBK1 inhibitor BX795 could downregulate IFN-I activation in PBMCs of SS, SLE, and MS patients ( 183 , 184 ). Compared to blocking common natural immune targets, such as TBK1 or IFNs, inhibition of cGAS-STING has less risk of immunosuppression and opportunistic infections without keeping the other PRR systems intact.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…The STING knockout cell line was a kind gift from Annemarie Steiner (Walter and Eliza Hall Institute of Medical Research, Parkville, Australia) and were generated using CRISPR/Cas9 gene editing as described previously 59 . In brief, gene deletion was induced in stably Cas9‐expressing HeLa cells by treatment of doxycycline (1 µg mL −1 , Sigma‐Aldrich) for 72 h to induce expression of STING ‐targeting sgRNA.…”
Section: Methodsmentioning
confidence: 99%